Supporting and Inhibiting Factors for the Sustainability of Tobacco Farmers' Businesses in Various Agroecosystems in Kediri Regency - Gabriella Maylani Prasetyaningrum; Lucky Rachmawati (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This study aims to analyze the factors that support and inhibit the sustainability of tobacco farmers' businesses in various agroecosystems in Kediri Regency. Methods: This study employed exploratory qualitative research methods, collecting data through in-depth interviews, observations, and document analysis from farmers, tobacco experts, companies, and the Agricultural Extension Agency. Results: The study indicates that the supporting factors for the sustainability of tobacco farmers' businesses include appropriate agroecosystem conditions, government support in the form of subsidies and training, as well as partnerships with the tobacco industry. However, the sustainability of this business also faces various obstacles, such as price fluctuations, dependence on intermediaries, limited access to capital and technology, and increasingly stringent regulations on the tobacco industry. Novelty: The differences in agroecosystems among the three sub-districts studied also impact the level of productivity and economic resilience of farmers. This study emphasizes the importance of government policies that are more pro-farmer and increasing access to more efficient agricultural technology to improve the competitiveness and welfare of tobacco farmers in Kediri Regency.